Antibody-coated microstructures for selective isolation of immune cells in blood. Issue 6 (26th February 2020) - Li, Jiyu; Liu, Ya; Ren, Jifeng; Tay, Benjamin Zikai; Luo, Tao; Fan, Lei; Sun, Dong; Luo, Guannan; Lau, Denvid; Marcos,; Lam, Raymond H. W.
Abstract : Selective immune cell isolation from diluted blood achieved with antibody-coated micropillar and micro-sieve structures in a microfluidic system. Abstract : Cell isolation from blood is an important process for diagnosing immune diseases. There are still demands for a user-friendly approach to achieve high cell extraction efficiency and purity of a target immune cell subtype for more promising diagnosis and monitoring. For selective immune cell isolation, we developed a microstructured device, which consists of antibody-coated micropillars and micro-sieve arrays, for isolating a target immune cell subtype from bovine blood samples. The focusing micropillars can guide immune cells flowing to the subsequent micro-sieves based on deterministic lateral shifts of the cells. The arrangement of these microstructures is characterized and configured for the maximal cell capture rate. Surface modification with a selected antibody offers selective cell capture in the micro-sieves based on the antigen–antibody reaction. We prepare a cell mixture of human CD14-expressing leukemia cells (THP-1) and epithelial cells (MDA-MB-231) in diluted blood to characterize the cell isolation operation, with a selective cell isolation yield of >80%, cell purity of ∼100% and cell viability of >93%. Together, this microstructured device strategy can achieve high-yield selective isolation of immune cells from blood samples and support downstream genetic and biochemical cell analyses, contributing to the medical diagnosis of a broad range of immune diseases.